2011
DOI: 10.4103/2229-4708.81088
|View full text |Cite
|
Sign up to set email alerts
|

Stress degradation studies and development of a validated stability-indicating-assay-method for determination of diacerein in presence of degradation products

Abstract: Background:To understand the degradation behavior of diacerein and to develop a simple, rapid, sensitive, and validated RP-HPLC method for the determination of diacerein, in the presence of its degradation products.Materials and Methods:An accurate, sensitive, precise, rapid, and isocratic reversed-phase high-performance liquid chromatography (RP-HPLC) method, equipped with a photo-diode array (PDA) detector for analysis of diacerein in the bulk drug has been developed and validated. The best separation was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…A validated stability-indicating HPLC methodology developed by Hamrapurkar et al 31 for the determination of rhein was utilized with slight modification. The HPLC instrument (Agilent 1260 Series high-performance liquid chromatography; Agilent Technologies, Santa Clara, CA, USA) with a reversed-phase C18 column (150 cm × 4.6 mm; PS =3.5 µm) was equipped with a security guard ULTRA cartridges HPLC C18 (4.6 mm) (Phenomenex, Torrance, CA, USA).…”
Section: Preparation Of Plasma Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…A validated stability-indicating HPLC methodology developed by Hamrapurkar et al 31 for the determination of rhein was utilized with slight modification. The HPLC instrument (Agilent 1260 Series high-performance liquid chromatography; Agilent Technologies, Santa Clara, CA, USA) with a reversed-phase C18 column (150 cm × 4.6 mm; PS =3.5 µm) was equipped with a security guard ULTRA cartridges HPLC C18 (4.6 mm) (Phenomenex, Torrance, CA, USA).…”
Section: Preparation Of Plasma Samplesmentioning
confidence: 99%
“…The perfusates were filtered, and an aliquot of 20 µL was injected into the HPLC system. The percentage of mucoadhesion was calculated using the following equation: hPlc of DcN and rhein A validated stability-indicting HPLC method 31 was used for the quantification of amounts of DCN permeated as rhein through the noneverted gut sac and amounts of DCN/rhein in the perfusate of the intestinal lumen after predetermined intervals. Calibration curves of DCN and rhein in the permeation medium (mixture of Krebs-Ringer phosphate buffer saline, pH 7.4, and isopropyl alcohol in the ratio of 7:3, v/v) and in the intestinal lumen washing medium (1:1 ringer to DMSO) over the concentration range of 1-50 µg/mL ( Figure S1) were obtained.…”
Section: Crystallinity Assessment Of Nanocrystalsmentioning
confidence: 99%
“…The review of the literature showed the presence of both spectrophotometric methods (Baghel, Dhiman, 2012;Nebsen et al, 2011;Pandey et al, 2012;Sivakumar et al, 2010) and chromatographic techniques (Ali et al, 2014;Ashok et al, 2009;Hamrapurkar et al, 2011;Patel et al, 2014;Sivakumar et al, 2010) for the estimation of DC from different formulations in presence of NSAIDs (Baghel, Dhiman, 2012), impurities (Ashok et al, 2009) and its corresponding metabolites from human serum (Ojha, Rathod, Padh, 2009). For the quantification of DS the pharmacopoeias present its non-aqueous titration in bulk forms and chromatographic procedures for various formulations (Dahivelkar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of a drug is defined as the ability of the drug to maintain its physical, chemical, biological and microbial properties during its shelf life [1]. The stability of every pharmaceutical product is affected by certain environmental conditions making stability one of the main important quality requirement for pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
“…One of such combination products is paracetamol/tramadol hydrochloride combination tablets. The development and validation of stability-indicating methods therefore helps to evaluate the drug product in the presence of its degradation products, excipients and other materials that might be present [1].…”
Section: Introductionmentioning
confidence: 99%